Implementation of islamic education curriculum development at stitma madani yogyakarta: A practical and theoretical review - Muhammad Shalahuddin Al Awwaby; Yusuf Ardhianto; Mohamad Agung Rokhimawan; Zulkifli Hayad; Aliwan (Yayasan Azhar Amanaa Yogyakarta, 2025)
The development of the Islamic Religious Education (PAI) curriculum in higher education plays a strategic role in shaping graduates who are not only intellectually excellent but also possess strong Islamic character. This article aims to examine in depth the processes of development, implementation, evaluation, and the challenges of the PAI curriculum at Sekolah Tinggi Ilmu Tarbiyah Madinatul Ilmi (STITMA) Yogyakarta. Employing a qualitative approach with a case study design, data were collected through interviews, observations, and document analysis. The findings show that STITMA applies an integrative curriculum approach that combines contemporary scientific knowledge with Islamic values, supported by active learning models such as project-based learning and the use of digital technology. Curriculum evaluation is conducted regularly and participatively, forming the basis for curriculum revisions that are aligned with real needs and national education policies. Despite challenges such as limited resources, resistance to innovation, and digital readiness issues, the development of the PAI curriculum at STITMA has shown a transformative direction that is adaptive and relevant to the demands of the times. This article recommends strengthening cross-sector collaboration and enhancing lecturer capacity as strategic steps to improve the quality of the PAI curriculum in the future.